2015
DOI: 10.1002/j.0022-0337.2015.79.1.tb05855.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Uncivil Student Behavior in Dental Education

Abstract: Students and faculty members in the health professions classroom are expected to exhibit professional behaviors that are conducive to maintaining a positive learning environment, but there is little published research concerning incivility in the area of dental education. The aim of this study was to evaluate differences in perceptions of incivility between dental faculty and students, between students in different courses of study, and between students in different years of dental study. The study utilized an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 18 publications
2
20
0
Order By: Relevance
“…Our study expanded on a previously published study concerning student and faculty perceptions of uncivil student behavior in dental education and used its survey as a basis for conducting this study 18 . The current study inquired about perceptions of faculty incivility in a dental education setting and found significant differences between faculty and students.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study expanded on a previously published study concerning student and faculty perceptions of uncivil student behavior in dental education and used its survey as a basis for conducting this study 18 . The current study inquired about perceptions of faculty incivility in a dental education setting and found significant differences between faculty and students.…”
Section: Discussionmentioning
confidence: 99%
“…Approval for administration of the survey was obtained from the Louisiana State University Health Science Center Institutional Review Board. This study used an electronic survey based on a previous survey that investigated perceptions of student incivility 18 . The survey consisted of 39 questions for student participants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The basis for the development of the survey entailed combining information gathered from the Incivility in Nursing Education-Revised and other surveys from the literature. 17,20,28,29 Our survey instrument consisted of 4 sections. Section I contained demographic questions such as gender, age, race/ethnicity, level of education, geographical location, years of teaching experience, program type, and type of learning environment (8 items).…”
Section: Methodsmentioning
confidence: 99%
“…4,8,12,13 A small number of studies found age and gender have a positive association with these differences in faculty-student perceptions. 6,13,14,[16][17][18][19][20] Predictors and other contributory factors of student incivility indicate the influences of stress, social norms, and consumerism and narcissism traits significantly impact a student's tendency to engage in uncivil classroom behaviors. [21][22][23] Furthermore, a lack of support from institutional administration was also cited as a primary contributor to faculty dissatisfaction regarding incidents of student incivility.…”
Section: Introductionmentioning
confidence: 99%